سید سلیمان ندوی بحیثیت سیرت نگار: ایک تحقیقی جائزہ (Al-Qamar, 2024)
The greatest tutor of all time is widely regarded as being the Prophet Muhammad (SAW). In the field of Seerah literature, several study researchers have so far conducted a great deal of work with a combination of passion and devotion. One of the most amazing aspects of the noblest personality of the Prophet Mohammad (SAW) is that people of all religions, regardless of their affiliation, have produced masterworks of literature. In this regard, each contributor has made an effort to absorb and share nuggets of wisdom, love, and sacred attachment with the Prophet of Islam (SAW) to the best of their abilities. One of the most notable figures in Seerah Writing is Allam Sayad Sulaman Nadvi, who is regarded as a significant pioneer in the field. He published a few works on Seerah, including Seeraat-un-Nabi (SAW), Khutbat Madras, Rahmat Alam, and Muhammad the Ideal Prophet. He also gathered a wealth of information on Seerah. The main goals of this article are to provide an overview of the scholarly literature on Seeraat un-Nabi and to emphasise Allama Sayad Sulaman Nadvi's biography.
Keywords: Seerah literature; Allam Sayad Sulaman Nadvi; Prophet Muhammad (SAW); Khutbat Madras; Rahmat Alam